Knowledge of danger signs in pregnancy and their associated factors among pregnant women in Hosanna Town, Hadiya Zone, southern Ethiopia - Mesele, Tiruye Tilahun; Syuom, Asmra Tesfahun; Molla, Eshetie Amare (Frontiers in Reproductive Health, 2023)
Background Danger signs in pregnancy can warn of maternal health problems. In developing African countries, including Ethiopia, the rate of maternal mortality is high. There is little knowledge of danger signs during pregnancy and their associated factors at the community level in the study area. Methods A community-based, cross-sectional study was conducted to assess knowledge about danger signs among pregnant women in Hosanna Zuria Kebeles between 30 June and 30 July 2021. A simple random sampling method was used to select eligible pregnant women. The sample size was proportionally allocated based on the number of pregnant women in each kebele. Data were collected in face-to-face interviews using a pretested questionnaire. The descriptive results were presented as proportions, whereas the analytic results were presented as adjusted odds ratios (AOR). Results The prevalence of good knowledge of danger signs in pregnancy was 259/410 (63.2%, 95% confidence interval (CI) 58.3–67.8). The most common known danger signs during pregnancy were severe vaginal bleeding (n = 227, 55.4%), followed by blurred vision (n = 224, 54.6%). In the multivariable analysis, the age of the respondent (AOR = 3.29, 95% CI 1.15–9.38), the tertiary education of the mother (AOR = 5.40, 95% CI 2.56–11.34), and the number of live births (AOR = 3.95, 95% CI 2.08–7.48) were statistically significant factors. Conclusion There was an adequate prevalence of knowledge of danger signs in pregnancy among pregnant mothers compared with different studies in Ethiopia and different countries. Advanced maternal age, the respondent's level of education, and the number of live births were found to be independent determining factors for the level of knowledge on danger signs in pregnancy among pregnant mothers. Health facilities and healthcare providers should focus on antenatal care and the age and parity of the mother when giving information about danger signs in pregnancy. The Ministry of Health should provide reproductive health services in rural areas and encourage education for women. Further studies need to be conducted and include danger signs in the three trimesters using a qualitative study design.